LEGAL REVIEW ON THE MISUSE OF ASSET DISCLOSURE DATA IN THE TAX AMNESTY PROGRAM IN THE CASE OF MONEY LAUNDERING CRIMINAL OFFENSES - Heru Karyono; Bambang Ali Kusumo (CV. RADJA PUBLIKA, 2025)
This study aims to analyze the misuse of data disclosed in the Tax Amnesty Program in the context of money laundering criminal offenses (ML). The Tax Amnesty, regulated by Law No. 11 of 2016, provides taxpayers the opportunity to disclose undeclared assets without the risk of criminal sanctions. However, the emergence of practices misusing this protected data, particularly in money laundering investigations, creates complex legal issues. This research uses a normative juridical approach to examine legislation, the principle of non-self-incrimination, and the role of law enforcement authorities in utilizing amnesty data. The findings of the study show a tension between the legal protection of data disclosed in this program and the authority of law enforcement agencies to investigate and act on potential money laundering. The study concludes that the use of Tax Amnesty data for criminal purposes, particularly in relation to ML offenses, must be done with caution to avoid violating fundamental principles of human rights protection and legal certainty.